2009
DOI: 10.1007/s00192-009-1020-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of treatment failure of midurethral sling procedures for women with urinary stress incontinence

Abstract: At a mean follow-up of 50 +/- 24 months (range, 12-114), the subjective cure rate was 84.7%. Multivariate analysis revealed that BMI >25 (OR, 2.9), mixed incontinence (OR, 2.4), previous continence surgery (OR, 2.2), intrinsic sphincter deficiency (OR, 1.9), and diabetes mellitus (OR, 1.8) are significant independent predictors for MUS failure. Concomitant prolapse surgery decreased the likelihood of surgical failure after MUS (OR, 0.6). Patient's age and the type of the sling were not found to be risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 25 publications
8
82
1
6
Order By: Relevance
“…Some other studies indicated these variables as independent risk factors for surgical outcome (14,15,16). In a recent study, it was reported that concomitant prolapse surgery decreased the likelihood of surgical failure after MUS (14), and that concurrent prolapse surgery, taking anticholinergic medications preoperatively and increased age were independent risk factors affecting successful outcome after MUS (16).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some other studies indicated these variables as independent risk factors for surgical outcome (14,15,16). In a recent study, it was reported that concomitant prolapse surgery decreased the likelihood of surgical failure after MUS (14), and that concurrent prolapse surgery, taking anticholinergic medications preoperatively and increased age were independent risk factors affecting successful outcome after MUS (16).…”
Section: Discussionmentioning
confidence: 98%
“…There are studies assessing the risk factors affecting cure and complication rates after MUS (14,15,16 and the cure rate was significantly lower in TVT patients over 55 years of age (18). However, there are also several studies that have demonstrated satisfactory outcomes after TVT in elderly patients (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pelvic organ prolapse and its correction did not significantly affect the cure rates [42]. In fact, a number of studies have shown that concomitant prolapse surgery decreases the likelihood of surgical failure after MUSs [55].…”
Section: Comparative Studies Of Tvt With the Transobturator Tapementioning
confidence: 92%
“…Risk factors for failure have been analyzed and were reported to be similar in the retropubic and transobturator MUSs. Stav et al [55] studied 1,225 women following MUS; multivariate analysis revealed that body mass index >25 (odds ratio (OR), 2.9), mixed incontinence (OR, 2.4), previous continence surgery (OR, 2.2), ISD (OR, 1.9), and diabetes mellitus (OR, 1.8) are significant independent predictors for MUS failure. Concomitant prolapse surgery decreased the likelihood of surgical failure after MUS (OR, 0.6).…”
Section: Management Of Recurrent Suimentioning
confidence: 99%
“…In 2012, Stav et al examined data from 1225 consecutive women with SUI receiving an MUS (955 retropubic and 270 transobturator) at their institution between 1999 and 2007. 3 Multivariate analysis showed that body mass index greater than 25 kg/m 2 , mixed incontinence, previous continence surgery, intrinsic sphincter deficiency, and diabetes are significant independent predictors for MUS failure. Conversely, patients undergoing concomitant prolapse surgery were at significantly lower risk of MUS failure (Table 1).…”
Section: Identification Of Patients At Risk For Failurementioning
confidence: 93%